2021
DOI: 10.1111/1365-2664.14056
|View full text |Cite
|
Sign up to set email alerts
|

Ecological memory and regional context influence performance of adaptation plantings in northeastern US temperate forests

Abstract: 1. Species distribution models predict shifts in forest habitat in response to warming temperatures associated with climate change, yet tree migration rates lag climate change, leading to misalignment of current species assemblages with future climate conditions. Forest adaptation strategies have been proposed to deliberately adjust species composition by planting climate-suitable species. Practical evaluations of adaptation plantings are limited, especially in the context of ecological memory or extreme clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Subsequently, this relationship is again modified by seed functional traits whereby differences in seedling survival are unaffected under mesic moisture regimes, but profoundly reduced for species with smaller seed masses relative to nursery transplants. These results are important when considered in the context of natural recruitment dynamics of forests under climate change relative to recent efforts to plant seedlings to enhance forest carbon stocks (e.g., reforestation, afforestation; Domke et al, 2020) or adapt species to shifting ranges (e.g., assisted migration; Clark et al, 2021;Palik et al, 2022). By testing sown seeds (analogous to natural regeneration), our results showed that future precipitation regimes may filter the germination and survival response for certain species (and traits), although these differences are less apparent for planted nursery stock.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, this relationship is again modified by seed functional traits whereby differences in seedling survival are unaffected under mesic moisture regimes, but profoundly reduced for species with smaller seed masses relative to nursery transplants. These results are important when considered in the context of natural recruitment dynamics of forests under climate change relative to recent efforts to plant seedlings to enhance forest carbon stocks (e.g., reforestation, afforestation; Domke et al, 2020) or adapt species to shifting ranges (e.g., assisted migration; Clark et al, 2021;Palik et al, 2022). By testing sown seeds (analogous to natural regeneration), our results showed that future precipitation regimes may filter the germination and survival response for certain species (and traits), although these differences are less apparent for planted nursery stock.…”
Section: Discussionmentioning
confidence: 96%
“…Four‐year survival of species planted in gaps (0.1 and 0.4 ha, combined results) to transition the composition of three forest types in New England, USA, to future conditions. The northern hardwood site is located on the Second College Grant (SCG), NH as part of the Adaptive Silviculture for Climate Change (ASCC) (Clark et al, 2021). Additional forest‐assisted migration (FAM) replicates include a spruce–fir–northern hardwood forest in Wolcott, VT (WOL) and a rich northern hardwoods forest in Washington, VT (WASH), USA.…”
Section: Case Studies Of Operational‐scale Fammentioning
confidence: 99%
“…Essentially, this process revolves around (1) planning for uncertainty by considering how the use of FAM within the climate adaptive strategies of resistance, resilience, and transition may support management goals, (2) assessing the specific application of FAM within a F I G U R E 5 Four-year survival of species planted in gaps (0.1 and 0.4 ha, combined results) to transition the composition of three forest types in New England, USA, to future conditions. The northern hardwood site is located on the Second College Grant (SCG), NH as part of the Adaptive Silviculture for Climate Change (ASCC) (Clark et al, 2021). Additional forest-assisted migration (FAM) replicates include a spruce-fir-northern hardwood forest in Wolcott, VT (WOL) and a rich northern hardwoods forest in Washington, VT (WASH), USA.…”
Section: Lessons From Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations